2017
DOI: 10.5194/bg-2017-320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic Ocean CO<sub>2</sub> uptake: an improved multi-year estimate of the air–sea CO<sub>2</sub> flux incorporating chlorophyll-a concentrations

Abstract: 28We estimated monthly air-sea CO 2 fluxes in the Arctic Ocean and its adjacent seas

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 1 publication
6
17
1
Order By: Relevance
“…Recently, Yasunaka et al. (2018) mapped all available pCO 2 observations in this region and determined an annual uptake of 180 ± 130 Mt C/yr over 1997–2014, including also the Bering Sea. We extracted fluxes for the Polar Sea and Barents Sea as defined here (Figure 1) from the mapped data published by Yasunaka et al.…”
Section: Review Of Relevant Processes and Conditionsmentioning
confidence: 99%
“…Recently, Yasunaka et al. (2018) mapped all available pCO 2 observations in this region and determined an annual uptake of 180 ± 130 Mt C/yr over 1997–2014, including also the Bering Sea. We extracted fluxes for the Polar Sea and Barents Sea as defined here (Figure 1) from the mapped data published by Yasunaka et al.…”
Section: Review Of Relevant Processes and Conditionsmentioning
confidence: 99%
“…We believe the broader uptake seasons for Boreal North America, Europe, and Russia, leading to stronger early summer land uptake in the case of VISIT a priori, caused positive CO 2 flux seasonality for the Northern Ocean. Even for the gc3t inversion case, we find the peak in the seasonal cycle in the summer season, when the oceanic biosphere activity is at its peak and pCO 2 in water is lower in summer than in the winter (Goto et al, 2017;Yasunaka et al, 2018). It is not easy to put forward a hypothesis for the weaker sink in summer than in winter of the Northern Ocean, while we can speculate that the atmospheric CO 2 decrease in polar air due to the strongest flux seasonal cycle on boreal land (Fig.…”
Section: Mean Seasonal Cycles Of Regional Co 2 Fluxesmentioning
confidence: 66%
“…9a, f, j) exceeds the decrease that occurs over the surface seawater and reduced solubility of CO 2 in warmer water. Indeed, Yasunaka et al (2018) have shown that the Greenland-Norwegian seas and the Barents Sea indeed act as a milder sink of CO 2 (flux = −4 to −5 mmol m −2 d −1 ) during June-August compared to the October-March (flux = −10 to −15 mmol m −2 d −1 ), and the Chukchi Sea and Arctic Ocean show the strongest uptake in October. Thus, as a whole, the Northern Ocean of our study could act as the weakest sink in the summer months.…”
Section: Mean Seasonal Cycles Of Regional Co 2 Fluxesmentioning
confidence: 99%
“…Annual methane emissions of the region vary from 0.0 to 4.5 Tg CH 4 yr −1 estimated by Berchet et al (2016). Yasunaka et al (2018) estimated the monthly air-sea CO 2 fluxes in the Arctic Ocean and adjacent seas located north of 60 • N for the period 1997-2014 and ended up at a net annual Arctic Ocean CO 2 uptake of 180 ± 130 Tg C yr −1 .…”
Section: Ocean Floor and Sediments: Composition And Fluxesmentioning
confidence: 99%
“…Operational sea ice analysis is increasingly important for Arctic shipping and navigation (Lei et al, 2015;Karvonen et al, 2017). New results on rare elements, mineral composition and CO 2 and methane fluxes associated with ocean sediments have been attained (Maslov et al, 2018b;Yasunaka et al, 2018). This serves as important information for mitigation plans as well as for new estimates of the river runoff and discharge in Russian rivers into the Arctic seas (Grigoriev and Frolova, 2018;Agafonova et al, 2017).…”
Section: Future Research Needs From the System Perspectivesmentioning
confidence: 99%